Morphological and Anatomical Characteristics of Taxus chinensis (Pilg.) Rehder in Thanh Hoa Province, Vietnam - Xuyen, Do Thi; Duc, Nguyen Anh; Hung, Lai Viet; Hai, Do Van; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology, 2023)
The Taxus chinensis  (Pilg.) Rehder belongs to the Taxaceae family, confer plants and is a rare and precious tree species of Vietnam which was recognized for its use value. The most of them are distributed in the high mountains of Vietnam. The resource values of this species were found as medicine, precious wood and an ornamental. So, looking back to the long history of use as well as overall research on species of the Taxus L. genus, the up-to-date reporting on Taxus chinensis is relatively much less extensive. These studies are an effort to understand the anatomical delimitation of Taxus chinensis  (Pilg.) Rehder in a better way and morphological characteristic with updated is provided. The comparative morphological and anatomical research method were used, Taxus chinensis  has dominent characteristic with winter bud scales, gather into a cone shape, early deciduous; leaves linear, thick textured; pale to white at abaxially because of the thick stomata bands.